Formulação e implementação computacional para verificação e composição de ábacos de seções de concreto armado submetidas à flexão oblíqua composta - Antonio Ribeiro de Oliveira Neto (2018)
Structural elements under axial load and biaxial bending are common in conventional reinforced concrete structures, in example, building columns. Such actionis characterized by a normal force and a bending moment that is not coincident with principal axes of inertia of the cross section area. In these cases, in design of reinforced concrete members, due to the interdependence between the variables, the determination of the neutral axes position does not present an explicit solution, thus, the calculation of the design capacity is given iteratively, resulting in a surface representing the cross section strength as know as the interaction diagram. The process of obtaining this surface depends on computational algorithms and, due to the constant updating and changes of national and international codes for design of reinforced concrete structures, it must be improved, expanded and in many cases redone. In this scenario, this work presents a formulation and computational implementation to calculate the load capacity and compose interaction diagrams of reinforced concrete cross sections under axial force and biaxial bending. It is also proposed, the composition of design charts. The formulation generalizes the load capacity obtention method, so that any cross-section and any constitutive law can be adopted, for instance, high strength concretes in accordance with 2014 version of the brazilian code for design of concrete structures, ber reinforced concrete or even structural steel.